Integrated Petrophysical and Seismic interpretation of Norne Field, Norway. - Khan, Adnan (UiT Norges arktiske universitet, 2014)
The aim of this thesis is to evaluate petrophysical properties and seismic interpretation of main reservoirs of Norne field in Mid Norwegian sea. Petrophysical evaluation helps in getting familiar with reservoir characterization using wireline logs data. The main concentration has been given to evaluate different reservoir properties i.e. porosity, shale volume, water saturation, hydrocarbon saturation, permeability and lithology indications. This petrophysical analysis indicates the quality of reservoirs and hydrocarbon presence. These studies show that reservoir in Norne field is of good to very good properties with average porosities ranges between 19% to 26%, water saturation from 20% to 36% in the hydrocarbon zone and 187 to 1087 mD. Seismic studies are carried to interpret the different horizons, faults and bounded structures. A total of six horizons were interpreted in 3D seismic dataset ST9203R03. Top Spek, Top Garn, Top Ile, Top Tofte, Top Tilje and Top Åre. The surface of Top Garn (Top reservoir) was of main interest of the interpretation. Through the interpretation , different geological features such as blocks, faults, floors and a trench were recognized.